Peptide Arrays Identify Isoform-Selective Substrates for Profiling Endogenous Lysine Deacetylase Activity - Gurard-Levin, Zachary A. (American Chemical Society, 2010)
[Image: see text] This paper reports the development of a class of isoform-selective peptide substrates for measuring endogenous lysine deacetylase (KDAC) activities in cell culture. The peptides were first identified by comparing the substrate specificity profiles of the four KDAC isoforms KDAC2, KDAC3, KDAC8, and sirtuin 1 (SIRT1) on a 361-member hexapeptide array wherein the two C-terminal residues to the acetylated lysine were varied. The arrays were prepared by immobilizing the peptides to a self-assembled monolayer of alkanethiolates on gold and could therefore be analyzed by a mass spectrometry technique termed SAMDI (self-assembled monolayers for matrix assisted laser desorption/ionization time-of-flight mass spectrometry). Arrays presenting the selective substrates were treated with nuclear extracts from HeLa, Jurkat, and smooth muscle cells and analyzed to measure endogenous deacetylase activities. We then use the arrays to profile KDAC activity through the HeLa cell cycle. We find that the activity profile of the KDAC3 selective peptide closely mirrors the changing acetylation state of the H4 histone, suggesting a role for this enzyme in cell cycle regulation. This work is significant because it describes a general route for identifying selective substrates that can be used to understand the differential roles of members of the deacetylase enzyme family in complex biological processes and further because the label-free approach avoids perturbation of enzyme activity that has plagued fluorescence-based assays.